SUSSAS E CURRALEIRAS KALUNGAS: na Folia do Divino Pai Eterno da cidade de Cavalcante-GO e na Festa de Santo Antônio da comunidade do Engenho II - RODRIGUES, Clênio Guimarães (2011)
This research describes and analyses Kalunga s community music during two important popular manisfestation, Folia do Divino Pai Eterno de Cavalcante-GO and Festa de Santo Antônio do Engenho II . During these traditional celebrations the Sussa and Curraleira are shown, two musical genre presenting a hybridized structure, form, harmony, melody, rhythm and instrumentation. From the study of a broad bibliographical survey a historical and socio cultural contextualization had been made, and established as a conceptual and theoric base for this research. A dialogical relation is stablisehd between these two musical genres, the people envolved in this process of creation and the respective performance space. On the other hand is visible the processes of socio-cultural exchange characterized by these music genres. These hybridization processes and social representation brings their identity. The data acquisition was made by direct and passive observations, semi-structured interviews and audio-visual recording. The descriptions take into account the expressive gestures and states on dense description and discursive representation. This research intends to contribute and fill the gap of the complex and rich Brazilian cultural music as well as compose bibliographic material for professors and students.